2009
DOI: 10.17221/42/2009-pse
|View full text |Cite
|
Sign up to set email alerts
|

Effects of co-cropping on bioaccumulation of trace elements in Thlaspi caerulescens and Salix dasyclados

Abstract: Most phytoremediation technologies are based on the use of selected plant species cropped as in monoculture. Separated (monoculture) and combined (simultaneous) cropping of hyperaccumulator Thlaspi caerulescens and accumulator tree Salix dasyclados were tested in our experiment. We used moderately and highly contaminated soil. Extremely contaminated soil caused progressive mortality of willows planted separately. Combined cropping with T. caerulescens enabled willows to survive. Generally, we determined decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The results obtained showed that the Cd hyperaccumulator + high-biomass Cd accumulator systems are always more efficient than high-biomass Cd accumulator + high-biomass Cd accumulator systems in extracting Cd from the soils. The most efficient intercropping system tested was T. caerulescens + Salix dasyclados , whose % Cd removal was 8.65%, being about 1.2× as high as that of a T. caerulescens monoculture (Fuksová et al, 2009). However, it should be noted that these studies, with one exception (Wu et al, 2007), were conducted in pots under controlled-environment conditions.…”
Section: Challenges and Emerging Interestsmentioning
confidence: 98%
See 2 more Smart Citations
“…The results obtained showed that the Cd hyperaccumulator + high-biomass Cd accumulator systems are always more efficient than high-biomass Cd accumulator + high-biomass Cd accumulator systems in extracting Cd from the soils. The most efficient intercropping system tested was T. caerulescens + Salix dasyclados , whose % Cd removal was 8.65%, being about 1.2× as high as that of a T. caerulescens monoculture (Fuksová et al, 2009). However, it should be noted that these studies, with one exception (Wu et al, 2007), were conducted in pots under controlled-environment conditions.…”
Section: Challenges and Emerging Interestsmentioning
confidence: 98%
“…For this reason, more field trials are needed to determine the real efficacies of various intercropping systems. Moreover, there is an important lesson from the previous studies that the Cd removed by hyperaccumulators often accounted for the majority (60–90%) of the total extracted by the intercropping systems (Fuksová et al, 2009; Wu et al, 2007). On this basis, it should be proposed that when considering the establishment of a successful intercropping system for enhancing Cd phytoextraction, one should attempt to enable a hyperaccumulator to achieve its maximum possible contribution in the system.…”
Section: Challenges and Emerging Interestsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some places, enormous concentrations of up to 4500, 8700 and 68 mg kg -1 for Pb, Zn and Cd, respectively, were detected here by Vaněk et al (2005). These soil conditions showed a high degree of phytotoxicity (Fuksová, Száková and Tlustoš 2009) where zinc was found to be the limiting element for plant growth and development at these concentration levels (Vysloužilová et al, 2003). The experimental field was located next to Trhové Dušníky village.…”
Section: Experimental Area and Designmentioning
confidence: 99%
“…With rapid industrialization, heavy metal pollution has become a serious threat to the environment in many countries (González-Oreja et al 2008;Zhang et al 2018). The heavy metal cadmium enters the environment through mining and smelting of metalliferous ores, industrial processes, heating systems, urban transportation, and phosphate fertilizer, and is considered one of the most prevalent toxic pollutants to plants, animals, and human beings (Mclaughlin et al 1999;Han et al 2002;Escarré et al 2011;Mahar et al 2016).…”
Section: Introductionmentioning
confidence: 99%